2015
DOI: 10.1017/s0007485315000061
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel microsatellite markers forHyphantria cuneaand implications for other Lepidoptera

Abstract: This is the first report of microsatellite markers (simple sequence repeats, SSR) for fall webworm, Hyphantria cunea (Drury) (Lepidoptera: Arctiidae), an important quarantine pest in some European and Asian countries. Here, we developed 48 microsatellite markers for H. cunea from SSR enrichment libraries. Sequences isolated from libraries were sorted into four categories and analyzed. Our results suggest that sequences classified as Grouped should not be used for microsatellite primer design. The genetic diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In this study, we observed a very high number of alleles per locus (average = 13.6) compared to other Lepidoptera species; 2.2 in Helicoverpa zea [ 36 ], 3 in Hyphantria cunea [ 37 ], 4.1 in Helicoverpa armigera [ 36 ], 4.6 in Carposina sasakii [ 38 ], 4.7 in Epirrita autumnata [ 35 ], 4.7 in Plutella xylostella [ 39 ], 7.0 in Chilo suppressalis [ 40 ], 8.8 in Zeiraphera diniana [ 41 ], and 10.5 in Parnassius apollo [ 42 ]. The large number of STR markers detected (2374) in this study enabled the possibility of selection of the most highly polymorphic markers.…”
Section: Discussionmentioning
confidence: 78%
“…In this study, we observed a very high number of alleles per locus (average = 13.6) compared to other Lepidoptera species; 2.2 in Helicoverpa zea [ 36 ], 3 in Hyphantria cunea [ 37 ], 4.1 in Helicoverpa armigera [ 36 ], 4.6 in Carposina sasakii [ 38 ], 4.7 in Epirrita autumnata [ 35 ], 4.7 in Plutella xylostella [ 39 ], 7.0 in Chilo suppressalis [ 40 ], 8.8 in Zeiraphera diniana [ 41 ], and 10.5 in Parnassius apollo [ 42 ]. The large number of STR markers detected (2374) in this study enabled the possibility of selection of the most highly polymorphic markers.…”
Section: Discussionmentioning
confidence: 78%
“…Heterozygote deficiency can be caused by the Wahlund Effect [ 31 ] or the presence of null alleles, for which Lepidoptera species are notorious [ 32 , 33 , 34 , 35 , 36 ]. It was considered that the present of null alleles is very common in this order due to the flanking region with repetitive sequences and multiple copies of loci [ 37 , 38 , 39 ]. Random sequences of C .…”
Section: Resultsmentioning
confidence: 99%
“…Eight of these loci exhibited an SNI. SNI mutation patterns can be complex, involving insertion/deletion (indel) events in flanking regions or may result from an excess of base substitutions 32 . Although these alleles can be identified manually, it is laborious and inaccurate.…”
Section: Discussionmentioning
confidence: 99%